Canonical and noncanonical inflammasomes in intestinal epithelial cells. (22nd July 2019) - Winsor, Nathaniel; Krustev, Christian; Bruce, Jessica; Philpott, Dana J.; Girardin, Stephen E.
Abstract: Inflammasomes are cytosolic, multimeric protein complexes capable of activating pro‐inflammatory cytokines such as IL‐1β and IL‐18, which play a key role in host defence. Inflammasome components are highly expressed in the intestinal epithelium. In recent years, studies have begun to demonstrate that epithelial‐intrinsic inflammasomes play a critical role in regulating epithelial homeostasis, both by defending the epithelium from pathogenic insult and through the regulation of the mucosal environment. However, the majority of research regarding inflammasome activation has focused on professional immune cells, such as macrophages. Here, we present an overview of the current understanding of inflammasome function in epithelial cells and at mucosal surfaces and, in particular, in the intestine.